2021
DOI: 10.3354/meps13611
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of juvenile American horseshoe crabs Limulus polyphemus in the Great Bay Estuary, New Hampshire, USA

Abstract: In order to effectively manage a fishery, it is important to know the essential habitats used by all life history stages of the species being managed. However, this is often a challenge for animals such as the American horseshoe crab Limulus polyphemus, whose juvenile stages are difficult to find and quantify. Visual surveys and suction sampling have been used in previous studies, but in the Great Bay Estuary, New Hampshire, they are less effective, and so little is known about the habitats occupied by juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…δ 34 S values measured in the current study further corroborate differences in movement, as adults appeared to have more enriched δ 34 S values compared to juveniles, indicating that adults migrate and access prey (e.g., bivalves) or SOM offshore that is more enriched in δ 34 S compared to the δ 34 S signatures of some estuarine organic matter sources (Rubenstein and Hobson 2004). Depleted δ 34 S values within juveniles could also be attributed to their tendencies to occupy mud-based habitats (Cheng et al 2021) that have higher sulfide concentrations from bacterial sulfate reduction (Brüchert and Pratt 1996). When considering these ontogenetic differences in space use, it appears that adults and juveniles exhibit moderate resource partitioning across space and time, which may be beneficial to reduce intraspecific foraging competition and may optimize fitness (Svanbäck and Bolnick 2007).…”
Section: General Foraging Patternssupporting
confidence: 82%
See 1 more Smart Citation
“…δ 34 S values measured in the current study further corroborate differences in movement, as adults appeared to have more enriched δ 34 S values compared to juveniles, indicating that adults migrate and access prey (e.g., bivalves) or SOM offshore that is more enriched in δ 34 S compared to the δ 34 S signatures of some estuarine organic matter sources (Rubenstein and Hobson 2004). Depleted δ 34 S values within juveniles could also be attributed to their tendencies to occupy mud-based habitats (Cheng et al 2021) that have higher sulfide concentrations from bacterial sulfate reduction (Brüchert and Pratt 1996). When considering these ontogenetic differences in space use, it appears that adults and juveniles exhibit moderate resource partitioning across space and time, which may be beneficial to reduce intraspecific foraging competition and may optimize fitness (Svanbäck and Bolnick 2007).…”
Section: General Foraging Patternssupporting
confidence: 82%
“…The lack of seasonal changes in resource use is not surprising for this life history stage given their localized movement patterns among estuarine habitats and low emigration from coastal estuaries (Bopp et al 2021). Juveniles have been observed to have a strong preference for subtidal mud substrates (Cheng et al 2021), which are richer in organic matter compared to coarser sediments (Serrano et al 2016), and may explain their assimilatory preferences for SOM. However, the constituents and quality of SOM often vary seasonally in temperate estuaries (Lesen 2006) and should be examined to determine its bioenergetic implications on horseshoe crab metabolism.…”
Section: General Foraging Patternsmentioning
confidence: 95%
“…If climate change results in more frequent storms, they could disrupt migrations, spawning phenology and egg survival. In addition, flooding causes freshwater intrusion, which could affect nursery and juvenile habitats in nearshore and intertidal environments proximate to spawning habitat (Bopp et al, 2021; Cheng, Chabot & Watson, 2021; Colon et al, 2022). In some spatial units, shifts in the spatial or temporal patterns of spawning could disrupt interspecific relationships and interfere with the populations achieving ecological functionality, such as a possible mismatch between shorebird migrations and horseshoe crab spawning in Delaware Bay (Smith et al, 2011; Tucker et al, 2019).…”
Section: Assessment Resultsmentioning
confidence: 99%
“…1988; Walls et al . 2002; Cheng et al . 2021), and studies have indicated that the area around the beach high tide line provides the best conditions for embryonic development (Penn and Brockmann 1994; Vasquez et al .…”
Section: Introductionmentioning
confidence: 99%
“…Horseshoe crabs are traditionally thought to spawn primarily on sandy beaches (e.g., Botton et al 1988;Walls et al 2002;Cheng et al 2021), and studies have indicated that the area around the beach high tide line provides the best conditions for embryonic development (Penn and Brockmann 1994;Vasquez et al 2015a,b). Due in part to the belief that horseshoe crabs spawn primarily on sandy beaches, horseshoe crab adult spawning and egg surveys have been conducted almost entirely in beach habitats (e.g., Smith et al 2002;Smith and Robinson 2015).…”
Section: Introductionmentioning
confidence: 99%